2019
DOI: 10.1038/s41467-019-08853-3
|View full text |Cite
|
Sign up to set email alerts
|

Global monitoring of antimicrobial resistance based on metagenomics analyses of urban sewage

Abstract: Antimicrobial resistance (AMR) is a serious threat to global public health, but obtaining representative data on AMR for healthy human populations is difficult. Here, we use metagenomic analysis of untreated sewage to characterize the bacterial resistome from 79 sites in 60 countries. We find systematic differences in abundance and diversity of AMR genes between Europe/North-America/Oceania and Africa/Asia/South-America. Antimicrobial use data and bacterial taxonomy only explains a minor part of the AMR variat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

29
587
6
16

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 780 publications
(638 citation statements)
references
References 46 publications
29
587
6
16
Order By: Relevance
“…A theoretical solution to the spread of AMR could be to use different drug classes in animals on the assumption that distinct antimicrobial selection pressures would sustain efficacy of drugs in humans. However, even if this was feasible, evidence from this study (and others (Hendriksen et al ., )) shows that multidrug resistant bacteria can be isolated and cultured from sewage, presenting a potential route for transmission of AMR in the environment. While the sources and implications of environmental contamination remain controversial (Rizzo et al ., ; Munck et al ., ), the evidence in our study is consistent with the horizontal transfer of AMR among Campylobacter isolated from livestock, humans and sewage.…”
Section: Discussionmentioning
confidence: 99%
“…A theoretical solution to the spread of AMR could be to use different drug classes in animals on the assumption that distinct antimicrobial selection pressures would sustain efficacy of drugs in humans. However, even if this was feasible, evidence from this study (and others (Hendriksen et al ., )) shows that multidrug resistant bacteria can be isolated and cultured from sewage, presenting a potential route for transmission of AMR in the environment. While the sources and implications of environmental contamination remain controversial (Rizzo et al ., ; Munck et al ., ), the evidence in our study is consistent with the horizontal transfer of AMR among Campylobacter isolated from livestock, humans and sewage.…”
Section: Discussionmentioning
confidence: 99%
“…In relation to hazard identification, as already mentioned under Section 3.5, metagenomics offers the possibility to produce in some cases consensus draft genomes of the strains of interest which would allow for a very rapid characterisation (virulence and AMR repertoire, among others) of the pathogenic strains present in a sample. For example, metagenomic sequencing of sewage has recently been suggested as a means of monitoring the occurrence of AMR genes in the general human population (Hendriksen et al., 2019b) and, in fact, AMR occurrence in wastewater treatment plants has been shown to mirror the clinical prevalence of phenotypic resistance in several bacterial species (Pärnänen et al., ).…”
Section: Assessmentmentioning
confidence: 99%
“…In relation to hazard identification, as already mentioned under Section 3.5, metagenomics offers the possibility to produce in some cases consensus draft genomes of the strains of interest which would allow for a very rapid characterisation (virulence and AMR repertoire, among others) of the pathogenic strains present in a sample. For example, metagenomic sequencing of sewage has recently been suggested as a means of monitoring the occurrence of AMR genes in the general human population (Hendriksen et al, 2019b) and, in fact, AMR occurrence in wastewater treatment plants has been shown to mirror the clinical prevalence of phenotypic resistance in several bacterial species (P € arn € anen et al, 2019). Shotgun metagenomics provides information on the complete pool of microbial genes from a particular sample, and therefore can be used to infer the full repertoire of resistance determinants within such sample, although depending on the approach those determinants might not be assigned to particular taxa and it is still difficult to obtain information on the AMR determinants harboured by specific bacterial strains.…”
Section: Metagenomics In Food-borne Outbreak Detection/investigationmentioning
confidence: 99%
“…Prescription levels for a particular antibiotic are unlikely to be of significant value in the surveillance of AMR in the regional community. Instead, determining the population resistome is significantly more informative 37 .…”
Section: Comparisons Between Oral and Gut Resistomes Reveal Differencmentioning
confidence: 99%